Home nothing sweet home: domestic violence in times of Covid-19 and the intersectionality gap in public policies (Research, Society and Development, 2020)
This work problematizes the intensification of domestic violence against women in times of the Covid pandemic19 during home isolation, with the intersectionality as a fundamental element in the formulation and implementation of public policies for the care, confrontation and combat of violence against women. The article aims to analyze the domestic violence suffered by women in times of Covid-19, thus addressing the patriarchal family and its consequences, such as the reserved home as a space for women and the necessary inclusion of intersectionality in the formulation of public policies for women. The methodological approach was qualitative and the type of descriptive and exploratory study, based on bibliographical research, in addition to the use of empirical data from some official websites, such as the World Health Organization and media such as El país and Globo. The study concluded that staying at home in times of social isolation may be the opposite of being safe and that public policies are not formulated from an intersectional perspective, so it is necessary that institutions that serve women in situations of violence need to be attentive and act in order to protect women's lives.